2010
DOI: 10.1063/1.3399775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal annealing on properties of InSbN grown by molecular beam epitaxy

Abstract: Role of native defects in nitrogen flux dependent carrier concentration of InN films grown by molecular beam epitaxy J. Appl. Phys. 112, 073510 (2012); 10.1063/1.4757031 Study of molecular beam epitaxially grown InGaAsSbN/GaSb single quantum wells J. Vac. Sci. Technol. B 29, 03C112 (2011); 10.1116/1.3555368Effect of the growth temperature and the AlN mole fraction on In incorporation and properties of quaternary III-nitride layers grown by molecular beam epitaxy J. Appl. Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…2). 19 The formation of In-N bonds leaves highly-reactive Sb atoms readily available for bonding to attain a thermodynamic equilibrium, which leads to other types of bonding, namely the Sb-N and In-N-Sb present in all our epilayers, and more likely to be formed during the nitridation process, as proposed in the anion exchange model of Lim et al 21 Although the presence of N-N interstitials were reported by Lim et al 20,24 in their InSbN epilayers, our epilayers did not reveal any XPS peak corresponding to N-N binding energy (303.8 eV) (not shown here). Hence, in our case Sb-N has been the major contributor of N-related point defects, which causes the lattice expansion as observed by Pham et al in their samples.…”
Section: H Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…2). 19 The formation of In-N bonds leaves highly-reactive Sb atoms readily available for bonding to attain a thermodynamic equilibrium, which leads to other types of bonding, namely the Sb-N and In-N-Sb present in all our epilayers, and more likely to be formed during the nitridation process, as proposed in the anion exchange model of Lim et al 21 Although the presence of N-N interstitials were reported by Lim et al 20,24 in their InSbN epilayers, our epilayers did not reveal any XPS peak corresponding to N-N binding energy (303.8 eV) (not shown here). Hence, in our case Sb-N has been the major contributor of N-related point defects, which causes the lattice expansion as observed by Pham et al in their samples.…”
Section: H Discussionmentioning
confidence: 77%
“…However, Lim et al 23 in excess N-N interstitials thereby increasing the background carrier concentration, which in turn blueshifted the absorption edge due to the Moss-Burstein effect. Rapid thermal annealing studies 24 in N ambient revealed a reduced background carrier concentration with an improvement in the crystalline quality and a maximum redshift in the absorption edge with a fundamental bandgap of 0.15 eV (8 lm). In the case of as-grown InSbN epilayers, Lim et al 23 reported the longest wavelength of 8 lm (0.15 eV) for an N incorporation of 0.2% observed for the layers grown at 380 C. They have also reported the reduction of misfit dislocations with the growth of two step buffers grown at 330 C and 380 C, respectively, as compared to a single buffer layer grown at 330 C.…”
mentioning
confidence: 99%
“…[1][2][3] Such alloys can be fabricated by molecular beam epitaxy, metalorganic chemical vapor deposition and low energy ion implantation and have been studied by several groups. [1][2][3][4][5][6][7][8][9][10][11][12] As it has been reported, the replacement of a few percent of Sb element by small, highly electronegative and isoelectronic nitrogen atoms in the binary InSb could result in a dramatic reduction of the fundamental band gap of approximately 100 meV per atomic percent of nitrogen. And negative bandgap can be realized by incorporation of a few percent of nitrogen occupying the anion lattice sites.…”
mentioning
confidence: 86%
“…Recently using an ex-situ annealing process, a lower electron concentration of ~2x10 16 cm -3 and an absorption wavelength edge near 8 µm was achieved [11]. However this process gives rise to a severe deteriorated surface which could limit the optical quality.…”
Section: Introductionmentioning
confidence: 99%